New perspectives on the historical geography and topography of Anatolia in the II and I millenium B.C.: [...most of the papers given on the International symposium "New Perspectives on the Historical Geography and Topography of Anatolia in the II and I Millenium B.C." held the 15th to 16th December 2006] (Eothen, 2008)
Literaturangaben